1994
DOI: 10.1007/bf01377123
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin (1,2-benzopyrone) for the treatment of prostatic carcinoma

Abstract: The unavailability of effective treatment for metastatic hormone-refractory and clinically localized but pathologically unfavorable prostatic carcinoma warrants trial of new and promising treatments. Preliminary studies in patients with metastatic disease have shown (a) subjective but no objective responses to 100 mg coumarin and cimetidine daily; (b) objective responses in 3 of 40 patients treated with 3 g coumarin daily, all of whom had normal performance status and 1 of whom remains with three resolved bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…A cumarina é um composto formado por um anel aromático fundido em um anel lactona com potencial para utilização de herbicida (Oliveros-bastidas et al, 2013), perfumes, cosméticos, cigarros (Sullivan, 1982), anti-inflamatório (Leal et al, 2000) além de fins medicinais, como na prevenção e tratamento de edemas consequentes da radioterapia e vários tipos de câncer (Grötz et al, 2001;Mohler et al, 1994;Thornes et al, 1994).…”
Section: Introductionunclassified
“…A cumarina é um composto formado por um anel aromático fundido em um anel lactona com potencial para utilização de herbicida (Oliveros-bastidas et al, 2013), perfumes, cosméticos, cigarros (Sullivan, 1982), anti-inflamatório (Leal et al, 2000) além de fins medicinais, como na prevenção e tratamento de edemas consequentes da radioterapia e vários tipos de câncer (Grötz et al, 2001;Mohler et al, 1994;Thornes et al, 1994).…”
Section: Introductionunclassified
“…Von Angerer et al [18] showed similar growth inhibition in several rodent prostate cancer cell lines, including a 40-50% decrease in pulmonary métastasés in the Dunning MAT-Lu tumor model. Mohler et al [19] reported objective responses in 3 of 40 patients with hor mone refractory osseous disease, including one with a durable response lasting longer than 4 years.…”
Section: Introductionmentioning
confidence: 99%
“…Estas atividades biológicas da cumarina podem, sem dúvida, explicar o aumento das taxas de perdas gestacionais encontradas neste estudo. Braun (1999) A cumarina é um produto vegetal natural amplamente utilizado como aditivo de perfume em diversos produtos (OPDYKE, 1974;COHEN, 1979) e que combinada com a cimetidina foi utilizada em ensaios clínicos para o tratamento de melanoma maligno, metastático de células renais carcinoma (MARSHALL et al 1994), e carcinoma da próstata (MOHLER et al, 1994). Também já foi utilizada como aditivo alimentar, prática esta interrompida devido a hepatotoxicidade (HAZLETON et al, 1956;HAGAN et al, 1967).…”
Section: A-d)unclassified